Biphenyl 4-Hydroxylases Involved in Aucuparin Biosynthesis in Rowan and Apple Are Cytochrome P450 736A Proteins . Issue 2 (10th April 2015) - Sircar, Debabrata; Gaid, Mariam M.; Chizzali, Cornelia; Reckwell, Dennis; Kaufholdt, David; Beuerle, Till; Broggini, Giovanni A.L.; Flachowsky, Henryk; Liu, Benye; Hänsch, Robert; Beerhues, Ludger
Abstract : A membrane-bound hydroxylase contributes to the biosynthesis of defense compounds in apple and related species. Abstract: Upon pathogen attack, fruit trees such as apple ( Malus spp.) and pear ( Pyrus spp.) accumulate biphenyl and dibenzofuran phytoalexins, with aucuparin as a major biphenyl compound. 4-Hydroxylation of the biphenyl scaffold, formed by biphenyl synthase (BIS), is catalyzed by a cytochrome P450 (CYP). The biphenyl 4-hydroxylase (B4H) coding sequence of rowan ( Sorbus aucuparia ) was isolated and functionally expressed in yeast ( Saccharomyces cerevisiae ). SaB4H was named CYP736A107. No catalytic function of CYP736 was known previously. SaB4H exhibited absolute specificity for 3-hydroxy-5-methoxybiphenyl. In rowan cell cultures treated with elicitor from the scab fungus, transient increases in the SaB4H, SaBIS, and phenylalanine ammonia lyase transcript levels preceded phytoalexin accumulation. Transient expression of a carboxyl-terminal reporter gene construct directed SaB4H to the endoplasmic reticulum. A construct lacking the amino-terminal leader and transmembrane domain caused cytoplasmic localization. Functional B4H coding sequences were also isolated from two apple ( Malus × domestica ) cultivars. The MdB4Hs were named CYP736A163. When stems of cv Golden Delicious were infected with the fire blight bacterium, highest MdB4H transcript levels were observed in the transition zone. In a phylogenetic tree, the three B4Hs were closest to coniferaldehyde 5-hydroxylases involved in lignin biosynthesis, suggesting a common ancestor. Coniferaldehyde and related compounds were not converted by SaB4H.